Kulturotwórczy i polityczny wymiar działalności edukacyjnej - Homa, Tomasz (Horyzonty Wychowania, 2017)
The reflection upon broadly understood education, its premises and aims to be achieved, as well as the ways in which they are specified, is the reflection upon all that society lives and feeds on, and aims at. Therefore, it is also the reflection on how society comprehends its common good and the way it shall be realised. This fact provides the reason for education including, essentially, two dimensions: culture-creating and political. Their specification, in the sphere of education, is naturally orbiting around the openly or secretly suggested ideal of man and citizen desired by a given society, or its particular group in power, influencing the process of defining educational aims and their ways of realisation. The reflections presented in this article do not aspire to exhaust the entire issue of culture-creating and political dimension of educational activity, but merely to bring out some, in our opinion important, traits. They also want to become an invitation to the reflection upon education and challenges it faces in the context of a broader debate over the shape of Poland in the process of democratisation, uniting Europe and the world exposed to the processes of globalisation.